2005
DOI: 10.1128/mcb.25.18.8064-8073.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in the STN1 Gene Triggers an Alternative Lengthening of Telomere-Like Runaway Recombinational Telomere Elongation and Rapid Deletion in Yeast

Abstract: Some human cancer cells achieve immortalization by using a recombinational mechanism termed ALT (alternative lengthening of telomeres). A characteristic feature of ALT cells is the presence of extremely long and heterogeneous telomeres. The molecular mechanism triggering and maintaining this pathway is currently unknown. In Kluyveromyces lactis, we have identified a novel allele of the STN1 gene that produces a runaway ALT-like telomeric phenotype by recombination despite the presence of an active telomerase p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
64
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 73 publications
8
64
3
Order By: Relevance
“…7D). This somewhat rapid shortening of stn1-13 telomeres is reminiscent of a telomere rapid deletion (TRD) phenotype described for an stn1 mutant of Kluyveromyces lactis (34). Intriguingly, we observed that stn1-13 could trigger the ILT pathway.…”
Section: Fig 8 Kinetics Of Telomeric Recombination In Rad52mentioning
confidence: 62%
“…7D). This somewhat rapid shortening of stn1-13 telomeres is reminiscent of a telomere rapid deletion (TRD) phenotype described for an stn1 mutant of Kluyveromyces lactis (34). Intriguingly, we observed that stn1-13 could trigger the ILT pathway.…”
Section: Fig 8 Kinetics Of Telomeric Recombination In Rad52mentioning
confidence: 62%
“…Such internal single-strand telomere sequences have been detected in both ''type II'' telomerase-deficient strains that survive senescence by employing a RAD52-and RAD50-dependent recombination pathway to maintain telomere function (Larrivee and Wellinger 2006). They have also been detected to some extent in the K. lactis stn1-M1 mutant strain (Iyer et al 2005). The type II survivor cells amplify their TG 1-3 telomere repeat sequences such that their terminal restriction fragments typically migrate on a Southern blot as a mix of distinct fragments.…”
Section: Nonoverlapping Regions Of Stn1p Interact With Ten1pmentioning
confidence: 73%
“…The type II survivor cells amplify their TG 1-3 telomere repeat sequences such that their terminal restriction fragments typically migrate on a Southern blot as a mix of distinct fragments. In contrast, in the stn1-186t, stn1-281t, and in the K. lactis stn1-M1 strains (Iyer et al 2005), telomerase is active and, in the case of the stn1-186t cells, sufficient for telomeres to appear as a heterogeneous smear. Thus, the loss of telomere integrity observed in the stn1-t strains has characteristics that distinguish it in comparison with other mutant strains that show end-protection defects.…”
Section: Nonoverlapping Regions Of Stn1p Interact With Ten1pmentioning
confidence: 93%
See 1 more Smart Citation
“…For instance, in S. cerevisiae, a cdc13-1 yku70 mutation at the semipermissive temperature caused type II survivors to form after a period of senescence-like growth without appreciably shortened telomeres (23). In K. lactis, a mutation in the telomereassociated protein Stn1 (stn1-M1) led to RTE that produced highly elongated and unstable telomeres and other features that distinguished it from the RTE of telomerase deletion survivors (33). The stn1-M1 cells had a chronic moderate growth defect but failed to display the large changes in growth rate that characterize senescence and survivor formation.…”
mentioning
confidence: 99%